Covid-19 Vaccination as A Condition of Carrying Out Limited Face-to-Face Learning in Universities - Ratih Christiana; Ibnu Mahmudi; Suharni Suharni (Universitas Kanjuruhan Malang, 2022)
This article aims to find out the reasons for Lecturers and Education Personnel who have not implemented Covid-19 Vaccination as a causal phenomenon and understand the behavior conditions in the community especially higher education units in Madiun City as a consequence phenomenon, viewed from a value perspective and community norms in accepting issue regarding Covid-19 Vaccination as one of the requirements for implementing limited face-to-face meetings learning. The method used is a qualitative method with the type of ecology psychology. Data analysis in this study was carried out inductively. The research subjects were determined purposively by considering the criteria are: Lecturers and Education Personnel at the University in Madiun City who have not been vaccinated for Covid-19. The results of the study show that positive verbal persuasion fosters efficacy for research subjects in making decisions regarding the perception of Covid-19 vaccination as a limited face-to-face meeting learning, otherwise, negative verbal persuasion increasingly makes research subjects carry out denial and self-defense the perception of Covid-19 vaccination as a limited face-to-face meeting learning. In Conclusion, is Covid-19 vaccination for lectures and education personnel, not a mandatory prerequisite for preparing and implementing limited face-to-face meeting learning in Universities in Madiun City.